The Impact of Edentulism and Periodontitis on Cognition - Lauren Berard; Miou Zhou (Taylor & Francis Group, 2024)
ABSTRACTBackground Masticatory dysfunction and periodontitis are independently linked to cognitive decline. This article aims to highlight the individual and common roles that periodontitis and tooth loss play in cognition. Specifically, we aim to summarize the behavioral effects on learning and memory that result from each pathology, explore mechanisms that may explain these effects, and review the commonalities between the two.Methods The PubMed database was used to implement searches of relevant clinical studies on the correlations between edentulism and cognitive decline as well as periodontitis and cognitive decline. Additional searches were done to investigate animal studies that provided behavioral and mechanistic findings to explain these relationships. The clinical and animal studies were summarized and analyzed in this review to reveal the commonalities and differences between these comorbidities.Results The clinical studies summarized in this review report significant correlations between both periodontitis and partial/full edentulism with cognitive decline. The behavioral and mechanistic findings in animal model studies are summarized to support the cognitive effects. Both in vivo and in vitro studies have identified key pathogens, molecules, or cellular pathways that contribute to a more comprehensive understanding of the pathophysiologic processes that link different types of oral disease to cognitive brain function.Practical Implications The correlation between oral disease and cognitive impairment has been well established but further exploration of the molecular and cellular mechanisms underlying these relationships can provide therapeutic implications and stress the importance of oral health and preventative care.AbbreviationsAD: Alzheimer's Disease; AFT: animal fluency test; BOP: bleeding on probing; BGI: biofilm-gingival interface; CAL: clinical attachment loss; CDT: clock drawing test; CERAD: Consortium to Establish a Registry for Alzheimer's Disease word learning test; CNS: central nervous system; CP: chronic periodontitis; DSST: digital substitution test; IL-1β: interleukin 1β; IL-6: interleukin 6; LC: locus coeruleus; MMP: matrix metalloproteinase; MMSE: Mini-Mental Status Examination; MoCA: Montreal Cognitive Assessment; MRI: Magnetic Resonance Imaging; MWM: Morris water maze; NO: nitric oxide; PDL: periodontal ligament; PISA: periodontal inflamed surface area; PP2A: protein phosphatase 2A; RABL: radiographic alveolar bone loss; RANKL: Receptor activator of nuclear factor-κB ligand; SCT: spatial copying task; TLR4: toll-like receptor 4; TNF-α: tumor necrosis factor α; Vmes: Mesencephalic trigeminal nucleus.